Paniguro: Feedforward in Interpersonal Communication - Moraga-Leaño, Melanie M. (Philippine Humanities Review, 2015)
This paper looks into the Western concept of feedforward in interpersonal communication in the context of the Filipino culture. The researcher formulated a model of the feedforward process in interpersonal communication which served as the conceptual framework of this study. A content analysis of published screenplays of three selected movies and three selected telemovies was done to study the manifestations of the use of feedforward in interpersonal communication in the context of the Filipino culture. Results show that Filipinos do employ feedforward. The functions of feedforward according to frequency of usage are as follows: (1) to preview the message; (2) to disclaim; (3) to open channels of communication; (4) to show perspicacity and empathy; and (5) to altercast. The first three functions are the same with its counterparts in the Western culture. The fourth function is a function unique to the Filipinos. The fifth function has slight variations with its Western counterpart. Feedforward as used by Filipinos in interpersonal communication is referred to as paniguro. The term paniguro was chosen by the researcher because feedforward is used to ensure that misunderstandings will be avoided or minimized. It is used to ensure that the message will be understood by the other communicator to show that they value the kapuwa. The researcher concludes that feedforward is a concept barely explored in the field of communication. This concept can and should be further explored as it provides us with a solution on how we can become better communicators in better interpersonal relationships.